Bétillon/Dorval-Bor - Bétillon/Dorval-Bory (2010)
Presentación de proyectos del estudio francés: Paysages en exil, Snow house, Teo boxes, Wes in Paris.
Keywords: BÉTILLON, RAPHAËL; DORVAL-BORY, NICOLAS; FRANCIA; ÎLE-DE-FRANCE; VILLE DE PARIS; PARIS; MIDI-PYRÉNÉES; HAUTE-GARONNE; TOULOUSE; CHILE; REGIÓN METROPOLITANA DE SANTIAGO; SANTIAGO DE CHILE; CONCURSOS; PREMIOS; ARQUITECTURA; ESTUDIOS DE ARQUITECTURA; INSTALACIONES; ARTE; REFUGIOS; REFUGIOS DE MONTAÑA; DISEÑO DE INTERIORES